AHASA RUPA TRADISI BALI DALAM WACANA SENI RUPA KONTEMPORER - Parta, I Wayan Seriyoga (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Self-educated Balinese artists develop Balinese visual art based fully on practices, diligence, and tenacity in creating their works so that they can master all the established techniques used in visual art production. Their long struggles in dealing with technical matters to process materials have enriched them with important experience and become the base of their technical knowledge. The self-creativity they possess, untouched by academic values, enable them to beat their collective unconsciousness. Thus, they can consciously create innovations in the visual language they are working on within their collective domain. This enables them to hold their own identity and to base their work on the values coming from their local culture. This kind of creativity can also play an important role in global context. On the other hand, many contemporary artists including istallation and textile artists have conducted a kind of critical reflection upon the social condition in which they live. The above situation creates optimism that the potential of the visual art in Balinese tradition may give various colors on the development of contemporary visual art.